2009
DOI: 10.1007/s10754-009-9070-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing hospital competition when prices don’t matter to patients: the use of time-elasticities

Abstract: Health care reforms in several European countries provide health insurers with incentives and tools to become prudent purchasers of health care. The potential success of this strategy crucially depends on insurers' bargaining leverage vis-à-vis health care providers. An important determinant of insurers' bargaining power is the willingness of consumers to consider alternative providers. In this paper we examine to what extent consumers are willing to switch hospitals when they are fully covered for hospital se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 24 publications
(26 reference statements)
1
39
1
1
Order By: Relevance
“…It was reported that availability of services proved to be positively correlated with catastrophic spending in low and middle income countries but not in high income countries [27,28]. In many other European countries health insurance coverage is very comprehensive and OOP payments are either absent or do not differ across provider alternatives [29]. In low and middle income countries, supply constraints limit the use of services, so countries with greater supply show higher levels of use and more financial catastrophe.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that availability of services proved to be positively correlated with catastrophic spending in low and middle income countries but not in high income countries [27,28]. In many other European countries health insurance coverage is very comprehensive and OOP payments are either absent or do not differ across provider alternatives [29]. In low and middle income countries, supply constraints limit the use of services, so countries with greater supply show higher levels of use and more financial catastrophe.…”
Section: Discussionmentioning
confidence: 99%
“…They find that the probability of bypassing a hospital decreases by between 2% and 10% when waiting times are less than the average. Travelling time is also considered in further work by [38] in order to estimate competition in the hospital markets. The effect of waiting times is summarised effectively by [33] using waiting time elasticities, using a case study of cataract surgery.…”
Section: Background: Discrete Choice Modellingmentioning
confidence: 99%
“…Consequently, patients may substitute distant healthcare providers for nearer ones due to differences in quality care, waiting times, and hospital reputation. [6][7][8][9] In certain cases, purchasers (insurers) have limited and/or specified healthcare providers from which their patients can seek treatment, and usually, purchasers' (insurers) bargaining power partly depends on patients' willingness to change provider. 5 In early 2012, Ghana's National Health Insurance Authority (NHIA) offered its enrolees in the Ashanti Region the option to choose their own primary healthcare providers via a patient list system called preferred primary healthcare provider (PPP).…”
mentioning
confidence: 99%